Մի հաշվերգի ոդիսականը - Ա. Ե. Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
Известная детская считалка "Ала-бала-ница" имеет болгарское происхождение. В Болгарии, как и в Армении "Ала-бала-ница" является самой популярной и любимой считалкой. "Ala-bala-nitsa", famous counting-out rhyme of the children of Armenia, is of Bulgarian origin. In Armenia, several variants are known, with different narratives. Interestingly, "Ala-bala-nitsa" is also the most popular and favourite counting-out rhyme in Bulgaria.
Keywords: Geography; Anthropology; Recreation; Folklore